Chemical Weathering of Layered Ni-Rich Oxide Electrode Materials: Evidence for Cation Exchange. Issue 7 (13th May 2017) - Shkrob, Ilya A.; Gilbert, James A.; Phillips, Patrick J.; Klie, Robert; Haasch, Richard T.; Bareño, Javier; Abraham, Daniel P.
Abstract : Lithiated ternary oxides containing nickel, cobalt, and manganese are intercalation compounds that are used as positive electrodes in high-energy lithium-ion batteries. These oxides undergo changes, when they are stored in humid air or exposed to moisture, that adversely affect their electrochemical performance. There is a new urgency to better understanding of these "weathering" mechanisms as manufacturing moves toward a more environmentally benign aqueous processing of the positive electrode. Delithiation of the oxide and the formation of lithium salts (such as hydroxides and carbonates) coating the surface, are known to occur during moisture exposure. The redox reactions which follow this delithiation are believed to trigger all the other transformations. In this article we suggest another possibility: namely, the proton – lithium exchange. We argue that this hypothesis provides a simple, comprehensive rationale for our observations, which include contraction of the c -axis (unit cell) lattice parameter, rock salt phase formation in the subsurface regions, presence of amorphous surface films, and the partial recovery of oxide capacity during electrochemical relithiation. The detrimental effects of water exposure need to be mitigated before aqueous processing of the positive electrode can find widespread adoption during cell manufacturing.